KEANDALAN BANGUNAN GEDUNG PASAR RAKYAT TEMATIK WISATA UBUD - PRAGANINGRUM, TJOKORDA ISTRI; PRADNYADARI, NI LUH MADE AYU MIRAYANI; SARASWATI, NI NYOMAN INTAN SAWITRI (GANEC SWARA, 2023)
Implementing building reliability is necessary to ensure the safety of all elements in the building. The Ubud Tourism Thematic People's Market is a 2-story building equipped with a basement. Located on Jl. Raya Ubud Nomer. 35, Ubud District, Gianyar, with a building area of 8,253 m2. This research aims to determine the level of reliability of the Ubud Thematic Tourism People's Market building. This research uses quantitative descriptive research methods. Data was obtained from a questionnaire guided by Minister of Public Works Regulation No. 29/PRT/M/2006 and Gianyar Regent Regulation Number 7 of 2023. Data analysis in this research was carried out using interview method and questionnaires. The interview method used purposive sampling with a sample of parties involved in the construction of the Ubud Thematic Tourism People's Market building, with a total of 26 respondents. The results obtained by the level of reliability of the Ubud Thematic Tourism People's Market building were divided into five, namely architectural reliability of 96.08% including reliable (95 - 100%), structural reliability of 95.92% including reliable (95 - 100%), reliability of utilities and fire protection is 96.25% including reliable (95 – 100%), reliability of accessibility is 95.76% including reliable (95 – 100%), and reliability of building layout and environment is 95.4% including reliable (95 – 100% ). The total reliability value of the Ubud Thematic Tourism People's Market building is 96.80%, including reliability (95 – 100%).